A treatise on the equilibrium of arches, in which the theory is demonstrated upon familiar mathematical principles - Gwilt, Joseph, 1784-1863 (John Weale, 1839)
The construction of an arch is one of the most important and curious operations in the science of architecture. This work investigates the pressures that take place amongst the materials whereof an arch is composed, and the method of arranging them so that the whole may remain at rest.